2019
DOI: 10.3906/sag-1812-165
|View full text |Cite
|
Sign up to set email alerts
|

Determination of liver fibrosis stages in Egyptian chronic hepatitis B patients by a noninvasive tool

Abstract: Background/aim: Hepatitis B virus (HBV) infection is the leading cause of liver fibrosis (LF). The prognosis and management of patients with chronic hepatitis B virus depend on the amount and progression of liver fibrosis. Angiopoietin-like protein 2 (Angptl2) is not only a chronic inflammatory mediator, but also a tissue-remodeling factor. The aim of this study is to explore the predictive value of Angptl2 in different fibrosis stages in patients chronically infected with HBV.Materials and methods: Eighty pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
1
1
1
Order By: Relevance
“…The AUROC value of the APRI scores in this study was lower than the value, 0.80, that was found by Wai et al (18). In other studies on patients with chronic HBV, the AUROC values ranged from 0.639 to 0.878 (31)(32)(33). Although our results were consistent with the studies in the literature, the low AUROC value that we found may be associated with the low number of patients that were included in the study, as well as the patient group, which consisted of young patients without significant fibrosis.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…The AUROC value of the APRI scores in this study was lower than the value, 0.80, that was found by Wai et al (18). In other studies on patients with chronic HBV, the AUROC values ranged from 0.639 to 0.878 (31)(32)(33). Although our results were consistent with the studies in the literature, the low AUROC value that we found may be associated with the low number of patients that were included in the study, as well as the patient group, which consisted of young patients without significant fibrosis.…”
Section: Discussioncontrasting
confidence: 78%
“…Our results were similar to the results of other studies in the literature. In the other studies, the AUROC value of FIB-4 was ranged from 0.646 to 0.812 for F≥2, and from 0.715 to 0.818 for F≥4 (31)(32)(33)(34). In our study, the FIB-4 score was more successful than the other non-invasive methods, APRI and ALBI, in terms of detecting the presence of significant fibrosis in patients with chronic HBV.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation